Global access to technologies to support safe and effective inguinal hernia surgery: prospective, international cohort study - ERGENÇ, MUHAMMER (My University, 2024)
Technological advancement is important to improve healthcare quality and safety, especially in surgery1. For patients with an inguinal hernia, mesh and minimally invasive surgery are the two main technologies that have improved healthcare quality and safety2,3. The use of mesh is proven to reduce recurrence4,5. This avoids the need for further repairs, which are technically more challenging and have a higher risk for patients6. The use of minimally invasive surgery has proven advantages in bilateral hernias and in female patients2,3and is recommended in unilateral repair where appropriate expertise is available2,3. Access to these technologies and the expertise required are not widely or equitably distributed at a global level. As it is the case for other technologies, countries in the Global South have more limited access1. At the same time, in this part of the globe, there is a higher prevalence and a higher burden of disease associated with inguinal hernias7. Several barriers to implementation in the Global South have been identified previously, including costs, distribution, and training8,9. To overcome these, studies reporting the use of mesh based on mosquito net mesh and evaluating training programmes have been conducted10,11. With these efforts and with global investment in new technologies and the expansion of existing technologies, it was expected that there would be an increase in their use in low–middle-income countries. Data assessing this variability have not been collected in a standardized way and are usually reported from single- country or single-region studies5,12. Therefore, identification of areas where improvement is most needed will be key to better inform policymakers. The overarching aim of this study was to evaluate access to technologies that are relevant to the treatment of inguinal hernia patients to identify the areas where improvement is needed. Therefore, the primary aim of this study was to evaluate the use of mesh and predictors of mesh use in elective inguinal hernia repairs and the secondary aims of this study were to evaluate the use of minimally invasive surgery and predictors of minimally invasive surgery use and to evaluate the safety associated with the use of mesh and the use of minimally invasive surgery.
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (MED); Clinical Medicine (MED)